2022
DOI: 10.1002/pan3.10395
|View full text |Cite
|
Sign up to set email alerts
|

The ecosystem services framework in archaeology (and vice versa)

Abstract: Economics, ecology and archaeology study various aspects of resource utilisation and mobilisation, differing in the studied systems, objects and currencies. However, the three disciplines have developed mostly independently, resulting in limited dialogue among them. Emergent fields such as ecological economics and environmental archaeology are now linking the three disciplines and promoting dialogue among them, but a theoretical framework that links all three disciplines at once is missing. I propose that ecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Additionally, this is in line with Grove & Rackham's theory (Grove & Rackham, 2001), stating that the present character of the Mediterranean landscape was likely achieved prior to many written records through a combination of increasing aridity and Bronze Age clearances between 3000-1000 BCE. In light of the sustainable and long-term management that can possibly be traced back to the Nuragic civilization, these agro-silvo-pastoral landscapes also represent cultural ES suppliers of important spiritual and cultural values (Katz, 2022). Crowded with nuraghi, they provide a marked sense of place and identity for Sardinia inhabitants, which consider the Nuragic civilization, together with their heritage, as the foundation of the Sardinian feeling of historical and cultural identity (Frongia, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this is in line with Grove & Rackham's theory (Grove & Rackham, 2001), stating that the present character of the Mediterranean landscape was likely achieved prior to many written records through a combination of increasing aridity and Bronze Age clearances between 3000-1000 BCE. In light of the sustainable and long-term management that can possibly be traced back to the Nuragic civilization, these agro-silvo-pastoral landscapes also represent cultural ES suppliers of important spiritual and cultural values (Katz, 2022). Crowded with nuraghi, they provide a marked sense of place and identity for Sardinia inhabitants, which consider the Nuragic civilization, together with their heritage, as the foundation of the Sardinian feeling of historical and cultural identity (Frongia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Katz (2022) claimed that incorporating archaeological knowledge in ES (and vice versa) would set better theoretical and knowledge‐based frameworks for understanding human resource management and utilization, human impact on the environment and sustainable natural resource management. Within the context of long‐term socio‐ecological dynamics, an ES‐archaeology nexus could offer decision‐makers lessons from the past and a broader perspective of sustainability (Guerry et al, 2015; López de la Lama et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances, it has been observed that the latter could even quadruple in number compared to other humanmodified contexts, where they are often threatened [29,[32][33][34][35][36]. Furthermore, vegetation cover may positively influence the conservation of monuments, as in the case of several hypogeal structures, via maintaining constant microclimatic conditions and thus limiting Sustainability 2023, 15, 16469 2 of 22 deterioration phenomena mainly due to water evaporation and phenomena of salt efflorescence [14,37,38]. Moreover, vegetation can provide interesting tools to define a preventive conservation plan, thereby reducing the weathering effect, protecting the monument and contributing to their conservation against aggressive weathering agents [39,40].…”
Section: Introductionmentioning
confidence: 99%